Contemporary Islamic Legal Debates on Egg Freezing (Oocyte Cryopreservation): A Maqāṣid al-Sharī'ah Perspective - Hudzaifah Achmad Qotadah; Syamsul Anwar; Yusdani Yusdani; Masithoh Masithoh; M. Muamar; Syafwendi Syafril (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Oocyte cryopreservation (egg freezing) has emerged as a transformative reproductive technology, yet its ethical and legal standing remains contested in Muslim-majority societies where reproductive decisions are deeply embedded in Islamic normative frameworks. This article examines contemporary Islamic jurisprudential responses to egg freezing through a cross-institutional analysis of scholarly discourse on fatwas and classical fiqh positions from major authorities including the International Islamic Fiqh Academy (IIFA), the Islamic Religious Council of Singapore (MUIS), and national fatwa committees in Indonesia and Malaysia. Employing a qualitative, library-based methodology, the study evaluates the compatibility of egg freezing with the foundational objectives of Islamic family law, particularly the preservation of lineage (ḥifẓ al-nasl), the protection of life (ḥifẓ al-nafs), and the safeguarding of human dignity (karāmah al-insān). Findings reveal an emerging juristic consensus permitting medically indicated egg freezing within a valid marital relationship, while social egg freezing remains deeply contested due to concerns over lineage ambiguity, marital continuity, and potential misuse following divorce or spousal death. This study contributes that a maqāṣid al-sharī'ah framework offers the most coherent normative basis for contemporary ijtihād on reproductive technologies, and concludes with recommendations for developing adaptive Islamic legal governance that upholds ethical integrity while accommodating responsible reproductive autonomy in an era of rapid biotechnological advancement.